A Comparative / Contrastive Study of Interviews in English And Arabic Languages: Donald Trump And Haidar Al-Abady As an Example - Hussein Al-Mi’mar, Shaima’Abdul (International Journal of Psychosocial Rehabilitation, 2020)
The media, as an important form of discourse, reflect and help shape the public’s opinions on different social issues. The Media and particularly broadcasts are important social institutions. They are important presenters of culture, politics, and social life, shaping as well as reflecting how these are formed and expressed (Bell, 1995: 68). Interview is considered as a formal meeting which a journalist puts a question to someone such as a famous person or Politician. It usually happens as Face to Face and with a person; it usually involves exchange talking between two or more persons. Although in some instances a conversation can be happen between people who types questions and answers back. It is always limited to a period of time, in the sense that the interview has a beginning (The opening) and an ending (The close of the interview) (Metzler,1977: 9) . The present study is a comparison between English and Arabic political interviews. It attempts to find whether political discourse in Arabic, is similar to that of English or not. The study aims at: 1. Conducting a theoretical study of interviews. 2. Analysing a representative sample of Arabic and English political interviews.3. Conducting a comparative study based on the results of the analysis as carried out above. 4. Drawing relevant conclusions. A representative sample of Arabic and English political interviews will be selected and analysed depending on Jucker (1986). The results of this analysis will be explained.